Analisis Penerimaan Penerapan PARIS (Parking Information System) dengan Metode Technology Acceptance Model (TAM) pada Area Parkir Stikom Surabaya - Khotimah, Dewi Ayu Khusnul; Nurcahyawati, Vivine; Erstiawan, Martinus Sony (Jurnal Sistem Informasi dan Komputerisasi Akuntansi (JSIKA), 2016)
This study aims to determine the perception of convenience and perceived benefit associated with the use of PARIS (Parking Information System) by adopting a model TAM 1 (Technology Acceptance Model), which consists of several constructs that perceived ease of use (X1), perceived usefulness (Y1), attitude toward behavior (Y2), behavioral intention (Y3) and behavior (Y4). This type of research is explanatory research with quantitative approach. Methods of data collection using questionnaires with sampling as many as 95 respondents from all users PARIS (Parking Information System) in Stikom Surabaya. Analysis of the data used is descriptive statistical analysis and path analysis (path analysis). Results from the study showed 7 construct to produce a significant effect, namely in the variable perceived ease of use (X1) to perceived usefulness (Y1), perceived ease of use (X1) to attitude toward behavior (Y2), perceived usefulness (Y1) to attitude towards behavior (Y2), perceived usefulness (Y1) to behavioral intention (Y3), attitude toward behavior (Y2) to behavioral intention (Y3), perceived usefulness (Y1) to the actual use (Y4) and behavioral intention (Y3) to behavior (Y4).